A Program of Their Own: The Design and Evolution of an Undergraduate Degree Program for Police Officers in Ontario - Deckha, Nitin (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2020)
In the late 1990s and early 2000s, the Toronto Police Service was exploring how to increase access to higher education to its officers. The service saw higher education as salient to its organizational imperatives of professionalization, increased public legitimacy and credibility, and enhanced academic recognition of police professional learning. To realize this mission, the Toronto Police Service entered into a higher education partnership with the University of Guelph and Humber Institute of Technology and Advanced Learning under its then-new joint venture, the University of Guelph-Humber. The University of Guelph-Humber designed an accredited higher education pathway for Toronto Police personnel that also gave academic credit for past professional learning and increased educational access by offering blended course delivery. Based on semi-structured interviews with key educational administrators at the University of Guelph-Humber, Humber Institute of Technology and Advanced Learning, and the Toronto Police Service, this article narrates the origins of this higher education pathway—a Bachelor of Applied Arts in Justice Studies. In addition, it describes how this pathway evolved to include non-uniform Toronto police personnel, other police services, and expanded further to include learners from the larger justice and public safety fields. The exploration is situated in a larger discussion about the relationship between higher education, professionalization and legitimacy, and the potential of partnerships between higher educational  institutions and professions in Canada.